Hamlet - Shakespeare, William, 1564-1616.; Spencer, T. J. B., (Terence John Bew), 1915-1978. (New York : Penguin, 1996)
Presents the text of Shakespeare's drama about the Prince of Denmark, and includes an introduction, a list of further reading, commentary, and a short account of the textual problems of the play.
Includes bibliographical references (p. 55-[60].
Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Princes -- Denmark -- Drama; Princes -- Drama; Denmark -- Drama